Deliar Noer’s Perspective on Identity Politics as Practiced by Islamic Political Parties - Fiqi Restu Subekti; Taufik Awan Wibowo (Austronesia Akademika, 2026)
This study examines Deliar Noer’s perspective on the practice of identity politics employed by Islamic political parties in Indonesia, particularly in relation to its implications for Muslim political unity, electoral strategy, and the substantive orientation of Islamic politics. The issue is important because identity politics has often been used as a political instrument to mobilize support, strengthen group solidarity, and construct electoral legitimacy. However, in practice, such politics may also produce social fragmentation, narrow political orientation, and symbolic contestation that does not necessarily contribute to solving public problems. Using a qualitative descriptive-analytical method, this study relies primarily on Deliar Noer’s relevant works and is supported by secondary literature concerning Islamic politics, political parties, and identity-based political mobilization in Indonesia. The findings show that Deliar Noer tends to view identity politics as a political tendency that brings more negative consequences than positive contributions. According to this perspective, identity politics may weaken the unity of the Muslim community, shift attention away from substantive public policy issues, and prioritize symbolic religious claims over programmatic political agendas. Nevertheless, Deliar Noer does not reject Islamic politics itself. Instead, he offers constructive evaluations by emphasizing reformist commitment, ukhuwah Islamiyah, cooperation among Muslim groups, the strengthening of Islamic education and economy, and the recognition of politics as a legitimate and strategic means of struggle. Therefore, Islamic political movements should ideally move beyond narrow identity-based mobilization and develop inclusive, solution-oriented, and programmatic agendas that advance justice, social welfare, and the broader public good